2022
DOI: 10.1039/d1fo04323d
|View full text |Cite|
|
Sign up to set email alerts
|

Protective mechanisms of Zanthoxylum bungeanum essential oil on DSS-induced ulcerative colitis in mice based on a colonic mucosal transcriptomic approach

Abstract: In this study, we used steam distillation to extract essential oil from the fruits of Zanthoxylum bungeanum Maxim. Based on GC-MS analysis, 45 volatile compounds in ZBEO were determined for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…Researchers have found that Cistanche deserticola extracts can improve oxidative stress, DNA damage, cell apoptosis, and inflammatory injury [ 27 , 28 ]. Additionally, Sichuan pepper [ 29 , 30 ], mugwort leaf [ 31 , 32 ], and Cyperus rotundus [ 33 ] contain volatile oils and their main constituents, which exhibit anti-inflammatory, antioxidant, and analgesic effects. Dried ginger can improve the pathological condition of the uterus in a Parkinson's disease rat model by modulating the ERK1/2/NF-κB signaling pathway mediated by transient receptor potential (TRP) ion channels [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that Cistanche deserticola extracts can improve oxidative stress, DNA damage, cell apoptosis, and inflammatory injury [ 27 , 28 ]. Additionally, Sichuan pepper [ 29 , 30 ], mugwort leaf [ 31 , 32 ], and Cyperus rotundus [ 33 ] contain volatile oils and their main constituents, which exhibit anti-inflammatory, antioxidant, and analgesic effects. Dried ginger can improve the pathological condition of the uterus in a Parkinson's disease rat model by modulating the ERK1/2/NF-κB signaling pathway mediated by transient receptor potential (TRP) ion channels [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The plant contains over 140 compounds, including polyphenols, alkaloids, lignans, coumarin, fatty acids, and essential oils (2,11,12). Beyond its polyphenolic content, constituents like hydroxy-alphasanshool, a mixed extract of fatty acids, and essential oil extraction from Z. bungeanum, have proven anti-inflammatory efficacious in various systems, such as the nervous system (127) and digestive system (140,141). As research progresses, the application of Z. bungeanum in both medical and daily contexts continues to broaden, promising potential benefits to human health.…”
Section: Discussionmentioning
confidence: 99%
“…ZBEO has demonstrated protective effects against DSS-induced colitis in mice. ZBEO doses of 20-80 mg/kg reduced myeloperoxidase activity, colonic pathological damage, colon length shortening, disease activity index, and DSS-induced weight loss (140,141). Administration of ZBEO significantly reduced IL-1b, IL-12 (140), TNFa, VCAM-1, TLR8, and IL-11 (141) mRNA levels.…”
Section: Z Bungeanum Essential Oilmentioning
confidence: 99%
See 1 more Smart Citation